Prevalensi dan derajat infeksi parasit pada ikan bandeng (Chanos chanos) di tambak tradisional - Ardany, Merry; Handayani, Leni (e-Journal BUDIDAYA PERAIRAN, 2021)
This study aimed to determine the prevalence and degree of parasitic infection in milkfish (Chanos chanos) cultivated in the Sungai Hukum and Segintung traditional ponds. This research was conducted in the traditional river pond areas of Sungai Undang and Segintung from March to May 2020. The sample used was 10 fish per pond obtained from the farmers' crops with a size of 29-37 cm and a weight of 223-354 grams. The data were analyzed descriptively. From the research results, in Sungai Undang pond found five types of parasites with a prevalence of Anisakis sp. (80%), Tricodina sp. (60%), Digenea (40%), Argulus sp. (40%), and Rhabdochona (20%), while in Segintung pond four types of parasites were found, namely Anisakis sp. (70%), Tricodina sp. (30%), Digenea (20%) and Rhabdochona (40%). The degree of parasite infection in traditional ponds was Anisakis sp. (2), Tricodina sp. (11), Digenea (2.75), Argulus sp. (2) and Rhabdochona (1.5). Meanwhile, in traditional ponds, bunches Anisakis sp (3,4), Tricodina sp. (2,7), Digenea (1,5) and Rhabdochona (2,75). The prevalence rate of parasites in milkfish in Sungai Undang traditional pond was higher than in the traditional Segintung pond, while the level of parasite infection rate in both ponds was similarly low, except that the parasite Tricodina sp in Sungai Undang pond was categorized as moderate infection.